Effect of particle size on the release behavior and functional properties of wheat bran phenolic compounds during in vitro gastrointestinal digestion. (15th January 2022) - Li, Yang; Li, Mengli; Wang, Lili; Li, Zaigui
Graphical abstract: Highlights: Release of phenols was dependent on the particle size of wheat bran. Monomer phenolic acid content varied with particle size before and after digestion. Free p -coumaric acid content in SWB increased by 373% before digestion. SWB showed higher ferulic acid bioaccessibility and better functional properties. Abstract: Wheat bran is a rich source of phenolic compounds, and the health benefits of phenolic compounds depend on its bioaccessibility. The release behavior and functional properties of phenolic compounds in different particle size wheat bran during in vitro digestion were investigated. Coarse wheat bran (CWB, 1110.39 μm) was milled by airflow impact mill to produce medium wheat bran (MWB, 235.68 μm), fine wheat bran (FWB, 83.73 μm) and superfine wheat bran (SWB, 19.16 μm). The reduction in particle size increased the release of phenolic compounds, mainly ferulic acid, after digestion. The free p -coumaric acid content in SWB was nearly five times higher than that in CWB, MWB and FWB due to the complete destruction of aleurone cell walls. Moreover, SWB showed higher bioaccessible phenolic compounds content (65.51%) than CWB. The improved phenolic bioaccessibility increased the antioxidant capacities and carbohydrate-digestive enzymes inhibitory activities of SWB and significantly reduced its starch digestibility.